Development of inositol-based antagonists for the D-myo-inositol 1,4,5-trisphosphate receptor. - Keddie, N; Ye, Y; Aslam, T; Luyten, T; Bello, D; Garnham, C; Bultynck, G; Galione, A; Conway, S (2011)
The syntheses of four D-myo-inositol 1,4,5-trisphosphate (InsP(3)) derivatives, incorporating phosphate bioisosteres at the 5-position, are reported. The methyl phosphate ester and sulfate derivatives retain InsP(3) receptor (InsP(3)R) agonist activity; the compounds that possess a methylphosphonate or a carboxymethyl moiety are InsP(3)R antagonists.